2012
DOI: 10.18388/abp.2012_2105
|View full text |Cite
|
Sign up to set email alerts
|

Dual, enzymatic and non-enzymatic, function of ecto-5'-nucleotidase (eN, CD73) in migration and invasion of A375 melanoma cells.

Abstract: Ecto-5'-nucleotidase (eN, CD73) mediates extracellular adenosine production from 5'-AMP. Non-enzymatic functions of eN have also been reported. The aim of the study was to investigate the role of ecto-5'-nucleotidase in aggressive melanoma behaviour. Analysis of the involvement of eN in adhesion, migration and invasion revealed eN functions unknown to date. We found that following eN blockade by concanavalin A, the strength of adhesion to different ECM proteins was not altered, but at the same time the invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 39 publications
3
78
0
Order By: Relevance
“…Since the CD73 protein was hardly detected on Western blots of HaCaT cells, compared to SQ20B cells, this suggests (i) that an additional post-translational control of CD73 exists in HaCaT cells, and (ii) that most of the CD73 protein is dedicated to enzymatic functions in HaCaT cells. As adhesion is believed to be controlled by the non-enzymatic activity of CD73 [18, 19], we propose that the residual CD73 protein detected in HaCaT cells may play a minor role in cellular adhesion. However, HaCaT cells have a much stronger basal adhesion than SCC61 and SQ20B cells (Supplementary Figure S2), thus indicating that this function mainly relies on a different pathway in this cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Since the CD73 protein was hardly detected on Western blots of HaCaT cells, compared to SQ20B cells, this suggests (i) that an additional post-translational control of CD73 exists in HaCaT cells, and (ii) that most of the CD73 protein is dedicated to enzymatic functions in HaCaT cells. As adhesion is believed to be controlled by the non-enzymatic activity of CD73 [18, 19], we propose that the residual CD73 protein detected in HaCaT cells may play a minor role in cellular adhesion. However, HaCaT cells have a much stronger basal adhesion than SCC61 and SQ20B cells (Supplementary Figure S2), thus indicating that this function mainly relies on a different pathway in this cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Putative binding partners of CD73, on cells or in the ECM, remain poorly defined. Sadej et al . have recently demonstrated that CD73 gene‐silencing in melanoma cells reduced migration on tenascin C and that this mechanism was independent of CD73 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…recently demonstrated that both enzymatic and non‐enzymatic functions of CD73 were involved in the aggressive behaviour of cancer cells. The enzymatic functions of CD73 were primarily involved in invasion of tumor cells, whereas non‐enzymatic effects of CD73 contributed to cell adhesion and migration …”
mentioning
confidence: 99%
“…In that sense, it is of note that eN functions not only just as the enzyme converting AMP to adenosine, but also as cell adhesion molecule (CD73), implicated in cell-cell and cell-extracellular matrix interactions (Vogel et al 1993;Olmo et al 1992). Specifically, eN establishes highly specific interactions with tenascin C and several other extracellular matrix proteins (Sadej et al 2008), whereas the interactions influence cell adhesion, migration, and adenosine generation (Sadej and Skladanowski, 2012). In support of the view, it has been recently shown that inhibition of metastatic potential in breast tumor cell lines was associated with impairment of cell motility due to a translocation of eN from random membrane distribution to clusters localized in microdomains (Terp et al 2013).…”
Section: Discussionmentioning
confidence: 99%